2011
DOI: 10.5558/tfc2011-009
|View full text |Cite
|
Sign up to set email alerts
|

Response of Breeding Songbirds to Vegetation Management in Conifer Plantations Established in Boreal Mixedwoods

Abstract: We examined the response of breeding songbird communities 11 years after four vegetation management treatments were applied. Post-treatment vegetation was characterized by manually interpreting large-scale aerial photography and estimating proportional cover of eight vegetation classes. Songbird abundance was assessed by territory mapping. Using GIS layers, number of registrations and average vegetation proportions were compared among treatments. Ordination of the relative abundance of the 11 most frequent bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…(), 352 Magura, Horvath, and Tothmeresz (), 353 Malumbres‐Olarte et al. (), 354 Paradis and Work (), 355 Raub, Hoefer, Scheuermann, and Brandl (), 356 Alberta Biodiversity Monitoring Institute (ABMI) (), 357 Arroyo, Iturrondobeitia, Rad, and Gonzalez‐Carcedo (), 358 Zaitsev, Wolters, Waldhardt, and Dauber (), 359 Kőrösi, Batáry, Orosz, Rédei, and Báldi (), 360 Littlewood, Pakeman, and Pozsgai (), 361 Moir, Brennan, Koch, Majer, and Fletcher (), 362 Carrijo, Brandao, de Oliveira, Costa, and Santos (), 363 Oliveira, Carrijo, and Brandão (), 364 Reis and Cancello (), 365 Zeidler, Hanrahan, and Scholes (), 366 D'Cruze and Kumar (), 367 Fabricius, Burger, and Hockey (), 368 Pelegrin and Bucher (), 369 Urbina‐Cardona, Londoño‐Murcia, and García‐Ávila (), 370 Chauvat, Wolters, and Dauber (), 371 Fiera (), 372 Savage, Wheeler, Moores, and Taillefer (), 373 Virgilio, Backeljau, Emeleme, Juakali, and De Meyer (), 374 Andersen, Ludwig, Lowe, and Rentz (), 375 Otto and Roloff (), 376 Zimmerman, Bell, Woodcock, Palmer, and Paloniemi (), 377 Hornung, Tothmeresz, Magura, and Vilisics (), 378 Magrini, Freitas, and Uehara‐Prado (), 379 Laurance and Laurance (), 380 Bragagnolo, Nogueira, Pinto‐da‐Rocha, and Pardini (), 381 Herrera, Wright, Lauterbur, Ratovonjanahary, and Taylor (), 382 Jung and Powell (), 383 Bartolommei, Mortelliti, Pezzo, and Puglisi (), 384 Andersen and Hoffmann (), 385 Armbrecht, Perfecto, and Silverman (), 386 Bihn, Verhaagh, Braendle, and Brandl (), 387 Buczkowski (), 388 Buczkowski and Richmond (), 389 Delabie et al. (), 390 Dominguez‐Haydar and Armbrecht (), 391 Fayle et al.…”
Section: Resultsmentioning
confidence: 99%
“…(), 352 Magura, Horvath, and Tothmeresz (), 353 Malumbres‐Olarte et al. (), 354 Paradis and Work (), 355 Raub, Hoefer, Scheuermann, and Brandl (), 356 Alberta Biodiversity Monitoring Institute (ABMI) (), 357 Arroyo, Iturrondobeitia, Rad, and Gonzalez‐Carcedo (), 358 Zaitsev, Wolters, Waldhardt, and Dauber (), 359 Kőrösi, Batáry, Orosz, Rédei, and Báldi (), 360 Littlewood, Pakeman, and Pozsgai (), 361 Moir, Brennan, Koch, Majer, and Fletcher (), 362 Carrijo, Brandao, de Oliveira, Costa, and Santos (), 363 Oliveira, Carrijo, and Brandão (), 364 Reis and Cancello (), 365 Zeidler, Hanrahan, and Scholes (), 366 D'Cruze and Kumar (), 367 Fabricius, Burger, and Hockey (), 368 Pelegrin and Bucher (), 369 Urbina‐Cardona, Londoño‐Murcia, and García‐Ávila (), 370 Chauvat, Wolters, and Dauber (), 371 Fiera (), 372 Savage, Wheeler, Moores, and Taillefer (), 373 Virgilio, Backeljau, Emeleme, Juakali, and De Meyer (), 374 Andersen, Ludwig, Lowe, and Rentz (), 375 Otto and Roloff (), 376 Zimmerman, Bell, Woodcock, Palmer, and Paloniemi (), 377 Hornung, Tothmeresz, Magura, and Vilisics (), 378 Magrini, Freitas, and Uehara‐Prado (), 379 Laurance and Laurance (), 380 Bragagnolo, Nogueira, Pinto‐da‐Rocha, and Pardini (), 381 Herrera, Wright, Lauterbur, Ratovonjanahary, and Taylor (), 382 Jung and Powell (), 383 Bartolommei, Mortelliti, Pezzo, and Puglisi (), 384 Andersen and Hoffmann (), 385 Armbrecht, Perfecto, and Silverman (), 386 Bihn, Verhaagh, Braendle, and Brandl (), 387 Buczkowski (), 388 Buczkowski and Richmond (), 389 Delabie et al. (), 390 Dominguez‐Haydar and Armbrecht (), 391 Fayle et al.…”
Section: Resultsmentioning
confidence: 99%
“…; 210 Otto and Roloff ; 211 Zimmerman et al. ; 212 Pelegrin and Bucher ; 213 Savage et al. ; 214 Bragagnolo et al.…”
Section: Resultsunclassified
“…As well, they indicate that these effects may be more persistent than previous studies suggest. Zimmerman et al (2011) recommend that songbird monitoring studies continue beyond the expected turnover time (i.e., the life expectancy of the resident population of songbirds at the time the treatment was applied) of the study populations. McLaren et al (1998) suggested a list of possible wildlife indicator species for monitoring the effects of forest management in boreal Ontario.…”
Section: Are Songbirds and Small Mammals Affected By Vegetation Managmentioning
confidence: 99%
“…Lautenschlager and Sullivan (2002), Guiseppe et al (2006), and NCASI (2009) recommended evaluating treatment effects at the species level in the context of how specific treatments affect habitat for the species. Zimmerman et al (2011) examine abundance of songbirds in relation to habitat within a replicated study 11 years after establishment of the conifer plantations. Vegetation management treatments included aerial application of herbicides (glyphosate and triclopyr), cutting (motor-manual cutting with brush saws and tractor-mounted Silvana Selective ® ), and untreated controls.…”
Section: Are Songbirds and Small Mammals Affected By Vegetation Managmentioning
confidence: 99%